The Aegean and the Orient in the Neolithic and Bronze Ages: The Evidence of Stamp and Cylinder Seals. Ph.D. Dissertation - Aruz, Joan (1986)
Adviser: G. Kopcke. – Order No. DA8626849. Cf. DissAbstr 47/08 (Febr. 1987) 3088-A